WORKSHOP PASIF INCOME: PENERIMAAN DIVIDEN SAHAM - Silviana Silviana; Wedi Rusmawan; Diana Sari; Nuryaman Nuryaman; Ahmad Fadjar; Rita Yuniarti; Adhitya Adhitya; Annisha Annisha; Sahrul Sahrul (LPPM Universitas Bina Bangsa, 2023)
The objective of this activity is to provide a combination of theoretical knowledge to young prospective investors. Participants in this activity are postgraduate students with diverse backgrounds, including banking professionals, entrepreneurs in various fields such as mining, steel, culinary, coffee shops, private hospital employees, and entrepreneurs. The activity is conducted through a semester-long workshop. The results of the activity indicate that passive income runs smoothly and successfully, with participants highly satisfied with the clarity and comprehensibility of the dividend material and the expertise of the speakers. The facilities, internet access, and air conditioning were excellent. Furthermore, the proposal for the next research activity (PKM) related to the theme of practicing buying and selling stocks in the capital market using software highlights a strong interest in further developing their investment knowledge